Primary hyperparathyroidism in young and adolescents: Alike or unlike adult hyperparathyroidism? - A series from South India - Dhalapathy Sadacharan; Smitha S Rao; Shriraam Mahadevan; G Shanmugasundar; S Murthy; Shruti Chandrashekaran; Vijay Bhaskar Reddy; Bharath Ramji (Indian Journal of Endocrinology and Metabolism, 2024)
Background: Primary hyperparathyroidism (PHPT) is a common endocrine condition but rare in the pediatric and adolescent populations. The presentations can be unique, accounting for significant morbidity in the case of untimely detection. Aim: To study surgically treated pediatric PHPT retrospectively. Methods: Surgically treated children of PHPT up to 20 years of age between 2010 to 2022 were analyzed. All of them were operated on by an endocrine surgeon and team. Results: There was a total of 712 parathyroidectomies over 12 years, out of which there were 52 children (7.3%) had PHPT at less than 20 years of age. This group included 32 male children. The mean age was 16.1 years, including 7 cases of neonatal severe HPT. Multiple Endocrine Neoplasia type 1 was confirmed in 12 children. Presentations were more severe like bone pain (35.13%), renal stones (27.02%), incidental asymptomatic detection (18.9%), failure to thrive (10.8%), and pancreatitis (8.1%) as compared to adults. Mean serum calcium was 12.9 mg/dl (highest-14.1, N-8.8-10.8 mg/dl), mean parathormone levels were 386.91 pg/ml (N-10-65) and vitamin D levels ranged from 2.9-22.8 ng/ml. Localization was done with ultrasound and 99mTc- SESTAMIBI scans. Mean serum calcium levels in NSPHPT were 28.6 mg/dl (N-8.8-10.8 mg/dl). There were a total of 45 cases (6.32%) of PHPT less than 20 years of age, excluding the cases of NSPHPT. All children underwent parathyroidectomy, with 14 cases having an additional thymectomy, 2 cases with thyroidectomy, and a single case of hemithyroidectomy. The cure rate was 97.3%, while one baby with NSPHPT had persistent disease (postop PTH-110 pg/ml). The uniglandular disease was seen in 54.05% and the rest had a multiglandular disease. Adults accounted for 559/660 cases with 80% uniglandular disease. All cases had a postoperative histopathological confirmation with an average follow-up of 1 year. Conclusion: Childhood PHPT has a few features same as the adult population. Symptomatic presentations like adults, though pancreatitis and fatigue were more commonly seen as compared to bone pain. Calcium, phosphorus, and parathormone levels were comparable. Uniglandular involvement was seen just like the adult population. There are a few others that make them a distinct subtype like their symptoms of bone pain and being more common among boys. One-fourth of them had MEN1. Fewer cases in this age group make them unique.